Hidden Curriculum Model: PAI Tutorial Program Collaboration in Building Religious Digital Literacy Awareness at Jambi University - Eva Iryani; Muhammad Sobri; Tuti Hardianti Hasibuan (MKWK PAI Universitas Jambi, 2023)
This study aims to provide an in-depth description of the phenomenon of implementing the hidden curriculum in collaborative learning of the Pai Tutorial Program in Building Awareness of Religious Digital Literacy at Jambi University. The main focus of this research approach is qualitative research. as quoted by Creswell Qualitative is a research approach that aims to understand what phenomena are presented by research topics such as behavior, perceptions, motives, and actions and others. Qualitative Approach This study aims to reveal data in related fields: Hidden Curriculum Model in the PAI Tutorial Program in building awareness of religious digital literacy and its application. As well as looking at the perceptions of students who take part in the tutorial program with the Hidden Curriculum model of digital literacy collaborative learning at the University of Jambi. The hidden curriculum is an invisible curriculum, can occur spontaneously, unplanned and can arise from learning experiences in schools. Even though the hidden curriculum does not have formal and measurable systematics, it plays a very important role in realizing a learning goal, especially PAI learning. PAI learning can be achieved optimally with hidden curriculum support through tutorial activities involving students outside class hours